2014
DOI: 10.1007/s10495-014-1045-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of VDAC1 prevents Ca2+-mediated oxidative stress and apoptosis induced by 5-aminolevulinic acid mediated sonodynamic therapy in THP-1 macrophages

Abstract: Ultrasound combined with endogenous protoporphyrin IX derived from 5-aminolevulinic acid (ALA-SDT) is known to induce apoptosis in multiple cancer cells and macrophages. Persistent retention of macrophages in the plaque has been implicated in the pathophysiology and progression of atherosclerosis. Here we investigated the effects of inhibition of voltage-dependent anion channel 1 (VDAC1) on ALA-SDT-induced THP-1 macrophages apoptosis. Cells were pre-treated with VDAC1 inhibitor 4,4'-diisothiocyanostilbene-2,2'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 61 publications
1
46
0
Order By: Relevance
“…Our results showed that HAC localized in the ER, lysosomes, Golgi apparatus and mitochondria. These findings clearly indicated that the mitochondria incurred apoptotic damage and corresponded well with the findings of related apoptosis studies [6,10]. While the present study demonstrated that HAC-SDT is capable of causing direct damage to mitochondria, the sonodynamic effect of HAC on the ER, lysosomes, and Golgi apparatus needs further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that HAC localized in the ER, lysosomes, Golgi apparatus and mitochondria. These findings clearly indicated that the mitochondria incurred apoptotic damage and corresponded well with the findings of related apoptosis studies [6,10]. While the present study demonstrated that HAC-SDT is capable of causing direct damage to mitochondria, the sonodynamic effect of HAC on the ER, lysosomes, and Golgi apparatus needs further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…ALA-SDT could generate ROS changing the VDAC1 channel properties in outer mitochondrial membrane, and then affected ER status to induce the macrophages apoptosis. 41 Wang et al 18 demonstrated that ALA-PpIX mainly accumulated in mitochondria and ER, and mitochondria played the key role in inducing the foam cell apoptosis. HY might partly induce macrophage apoptosis through ER, except mitochondria.…”
mentioning
confidence: 99%
“…Studies have shown that [Ca 2+ ] i overload is associated with mitochondria dysfunction and cell apoptosis (Chen et al, 2014;Orrenius et al, 2015). Accordingly, we next investigate whether PC-EEF induces mitochondria damage and cell apoptosis in K562 cells.…”
Section: Pc-eef Triggers Mitochondrial-dependent Apoptosis In K562 Cellsmentioning
confidence: 95%